Slow 5-cycles and their Special Properties Heard in World Music - John Roeder (Analytical Approaches to World Music)
This essay develops and applies a theoretical language for describing a special family of musical cycles that feature five elements at very slow tempos, with the aim of appreciating the listening experiences they afford. Referring to experimentally determined constraints on the perception and memory of duration and content, it shows that slow 5-cycling occupies liminal cognitive territory in which sequential expectations begin to dominate over timing expectations. To explore the nature and variety of effects that are possible in this process, it presents transcriptions and analysis of five examples of world music of diverse genres and cultures—work song, ritual, and entertainment— and in a range of textures including solo, choral, call-and-response, and polyphony. Through analysis of grouping, pulse salience, and durational projection–that is, of the features that inform listeners’ sequential and timing expectations—it shows how slow 5- cycles afford some temporal experiences that differ from those in the more common fast 5-cycles, and that they can differ from each other substantially.